Technology Utilization and Culinary Skills Among Public Senior High School Home Economics Learners in Legazpi City Division - Melecio, Richell (JPAIR Multidisciplinary Research, 2026)
Technology has transformed vocational education, particularly in culinary arts, by bridging theory and practice. This descriptive-correlational study examined the influence of technology use on the culinary skills of 176 Grade 11 and 12 Home Economics students in five public senior high schools in the Legazpi City Division during the 2026 academic year. School-profile variables included equipment availability, teacher specialization, teacher training, and industry cooperation; student outcomes measured were competence in cooking techniques, food safety, nutrition, and menu planning. Weighted means indicated that technology use was highly evident (WM = 4.35), with teacher specialization and training as the strongest drivers of technology adoption. Although students demonstrated high proficiency in cooking techniques and food safety, Spearman’s rho correlation revealed a negative association between differences in technological infrastructure and overall culinary competence. According to Fuentes and LaBad 2025 greater technology availability did not predict higher student competence. Instead, universal pedagogical practices and repeated hands-on cycles (teacher expertise and instructional design) were more closely associated with student performance. The findings suggest that basic technology is necessary but insufficient; human factors, particularly teacher specialization and training, are critical determinants of culinary competence. For policy and instruction, the study recommends implementing the TECH-CUL initiative, which pairs targeted investments in essential equipment with systematic teacher training and strengthened school–industry partnerships to address resource and exposure gaps and improve student outcomes.